2013
DOI: 10.1042/bj20130807
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial fission mediates ceramide-induced metabolic disruption in skeletal muscle

Abstract: Ceramide is a sphingolipid that serves as an important second messenger in an increasing number of stress-induced pathways. Ceramide has long been known to affect the mitochondria, altering both morphology and physiology. We sought to assess the impact of ceramide on skeletal muscle mitochondrial structure and function. A primary observation was the rapid and dramatic division of mitochondria in ceramide-treated cells. This effect is likely to be a result of increased Drp1 (dynamin-related protein 1) action, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(95 citation statements)
references
References 49 publications
4
86
1
Order By: Relevance
“…Despite being necessary to cellular health, ceramides mediate multiple pathological cellular processes [17,18,19], including forcing sustained mitochondrial fission [8]. Due to our findings of reduced mitochondrial fission in myotubes following β-HB treatment, we probed ceramide levels and found a small but significant reduction in multiple ceramide species, including C16, C22 and C24 (Figure 4).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Despite being necessary to cellular health, ceramides mediate multiple pathological cellular processes [17,18,19], including forcing sustained mitochondrial fission [8]. Due to our findings of reduced mitochondrial fission in myotubes following β-HB treatment, we probed ceramide levels and found a small but significant reduction in multiple ceramide species, including C16, C22 and C24 (Figure 4).…”
Section: Resultsmentioning
confidence: 98%
“…We previously found that mitochondrial morphology alters mitochondrial physiology, including respiration and reactive oxygen species production [8]. In an effort to better understand a potential non-energetic mechanism whereby β-HB alters mitochondrial respiration, we scrutinized mitochondrial morphology and amount in C2C12 myotubes following β-HB treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, there is evidence that ceramides accumulate within the skeletal muscle and promote the oxidative stress and mitochondrial dysfunction (Coen & Goodpaster, 2012; Smith et al ., 2013). Second, the accumulation of ceramide within the myocardium (lipotoxicity) has been recently proposed as a major cause of dilated cardiomyopathy in patients with diabetes and obesity and as a potential mechanism for the development of heart failure, even in the absence of hypertension and myocardial ischemia Park and Goldberg, 2012.…”
Section: Discussionmentioning
confidence: 99%
“…This has been associated with the development of insulin resistance as well as altered mitochondrial respiratory activity (50,132). Importantly, administration of pharmacological inhibitors of de novo ceramide synthesis [e.g., the serine palmitoyltransferase (SPT) inhibitor myriocin] has been shown to ameliorate the insulin-desensitizing effects of dietinduced obesity as well as promote improvements in whole body oxygen consumption and mitochondrial function (146,156).…”
Section: The Ecs-mitochondrial Axis: Mechanistic Insightsmentioning
confidence: 99%